2007
DOI: 10.1007/s00066-007-1740-z
|View full text |Cite
|
Sign up to set email alerts
|

Surgery and Chemotherapy for Small Cell Lung Cancer in Stages I–II with or without Radiotherapy

Abstract: Surgical tumor resection may be considered for carefully selected patients. Adjuvant chemotherapy and PCI are recommended for all patients. Adjuvant TRT is currently used in patients with positive lymph nodes (pN1), because the probability of a subclinical involvement of the mediastinal lymphatic system appears to be increased in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Surgical resection which has been showed to improve overall survival in some studies (21) but fails to improve survival in the study by Lad et al (22) which included 340 patients with stages I to IIIB SCLC. However, some retrospective studies showed an 86% benefit of surgery for stages I and II on 5-year survival (23), a 47% benefit of surgery for stages IA to IIB (24,25), and decreased overall survival with increasing stages. Results of this study also showed that surgery improved overall survival for N0, N1, and N2 (N3 stages were excluded from the study) and postoperative radiotherapy for N2 subgroup but not for N0 and N1 subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection which has been showed to improve overall survival in some studies (21) but fails to improve survival in the study by Lad et al (22) which included 340 patients with stages I to IIIB SCLC. However, some retrospective studies showed an 86% benefit of surgery for stages I and II on 5-year survival (23), a 47% benefit of surgery for stages IA to IIB (24,25), and decreased overall survival with increasing stages. Results of this study also showed that surgery improved overall survival for N0, N1, and N2 (N3 stages were excluded from the study) and postoperative radiotherapy for N2 subgroup but not for N0 and N1 subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer death for men and the third for women in Japan [2,16,17,20]. As for stage I non-small cell lung cancer (NSCLC), surgical resection results in 60-70% 5-year overall survival rates [4,9].…”
Section: Introductionmentioning
confidence: 99%
“…Esophagitis is an important side effect during thoracic radiotherapy, and becomes dose-limiting when radiation doses > 60 Gy are used, especially in combination with chemotherapy [2,4].…”
Section: Introductionmentioning
confidence: 99%